Short range electromagnetic interface using 0.35 lm CMOS blocks for temperature monitoring in isolated areas - Sotner, Roman; Jerabek, Jan; Polak, Ladislav; Prokop, Roman; Ayten, Umut Engin; Jaikla, Winai (ELSEVIER, 2022)
Introduction: Infra-red (IR) and visible light (VL) based systems developed for transmission of informa-tion about physical quantities (e.g. humidity, temperature) out from closed areas, cannot be effectively employed in case of specific conditions in a targeted environment (because of fog or vapor for example). Objectives: In this work, we introduce a concept of wireless short-range transmitter and receiver to sense physical quantities, for instance temperature, with slow variation. The proposed concept is able to trans-mit analog-based information from isolated environments (e.g. aquariums or environments for plant growing) with high immunity against vapor and fog that limits standard optical (laser, IR band) methods of communication. Methods: In this work, a new concept of short range radiofrequency (RF) communication device consist-ing of transmitting and receiving parts build from active devices fabricated in 0.35 lm I3T25 3.3 V CMOS process and ferrite antennas is selected. RF part uses medium-wave propagation within 10 mm distance at frequency 700 kHz. Such an approach offers minimal path loss of the radiated energy of a signal and low-gain amplification required for restoration of similar levels as available at the transmitting side. Results: The processing of base-band signals of simple (sine wave) and complex (electrocardiogram) character was verified experimentally through the system. Application example of temperature monitor-ing in a closed environment, based on a temperature sensor (thermistor), verifies operationability in tem-perature range from 10 degrees C up to 50 degrees C. Conclusion: Compared to state-of-the-art solution, the presented concept has several advantages, for instance: less complexity; using of simpler type of modulation and demodulation; lower power con-sumption and significantly reduced issues caused by an environment with special transmission condi-tions (e.g. fog and vapor). The obtained results are in good agreement with expectations. Among others, the presented system brings beneficial performances for similar applications targeting on moni-toring of low-frequency or slowly varying signals.(c) 2022 The Authors. Published by Elsevier B.V. on behalf of Cairo University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Active elements; Amplitude modulation; ASIC; CMOS; Electronic adjustment; Medium radiofrequency wave; Temperature monitoring; COMMUNICATION; Science & Technology - Other Topics